Artisanal Fisheries, Food Security, and Sustainable Resource Management in Coastal Communities of Southern Madagascar - Saloa Taquidine Darousse; Raberinary Daniel; Mbola Mampiray Miandrito (Ite Ngabdi, 2026)
Artisanal fisheries are fundamental to the livelihoods, food security, and economic resilience of coastal communities in southern Madagascar, yet increasing fishing pressure and environmental change threaten their long-term sustainability. This study examined the contribution of artisanal fisheries to household food security and sustainable resource management using a mixed-methods approach. Primary data were collected from 320 fishing households and 96 non-fishing households across six coastal communities through household surveys, fisheries landing observations, key informant interviews, and focus group discussions. Household food security was assessed using the Food Consumption Score (FCS) and the Household Food Insecurity Access Scale (HFIAS), while fisheries productivity was evaluated using Catch per Unit Effort (CPUE). Multiple linear regression was employed to identify the socio-economic determinants of household food security. The results indicate that fishing households generally achieved higher food security than non-fishing households, although a significant decline in CPUE suggests increasing pressure on marine resources. Livelihood diversification emerged as the strongest predictor of household food security, followed by fishing income and market accessibility. The findings highlight the need for integrated policies that combine sustainable fisheries management, livelihood diversification, and improved market access to enhance household resilience while ensuring the long-term sustainability of coastal fisheries in southern Madagascar.